Third Five Year Plan (1961-66) Tripura Administration - Planning Commission (Planning Commission, 1963)
In the fight for economic advancement, all plans are a, part of a common strategy. The Third Plan will be merely a continuation and intensification of what has been achieved or attempted already. The achievements in the Second Plan will provide the starting point and the mistakes and shortfalls will be pointers for future action. What has already been achieved will be consolidated and the- economic benefits flowing there from utilized to the maximum. New schemes have been for. med keeping in view the further needs of the territory. The present Union Territory of Tripura with an area of roughly 4000 sq miles was a Princely State. The country is undulating and was covered at one time with fairly dense forest. The original population was primarily tribal who made a living out of shifting cultivation a form of primitive agriculture.
Tripura Administration
Tripura Administration
Keywords: Scheme For The Extension of The Tripura Administration; Expansion of Plant Protection measure; Implementation of The Proposal; Improved Agricultural Practices; Agricultural Workshop; Scheme For Development of Jute; Cotton Development; Establishment of Are Can’t Nursery; Farm Planning; Dairying & Milk Supply; Community Development; strengthening of the directorate of industries Introductory Memorandum of Forestry Scheme.